PENGARUH MEDIA EDUKASI QUIZIZZ TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AQIDAH AKHLAK KELAS VIII MTs AR-ROFIQY KABUPATEN BOGOR - Nafisa, Adilla; Lisnawati, Santi (Inspiratif Pendidikan, 2022)
Learning usingeducational media Quizizz can improve student learning outcomes, so teachers need to know the media criteria that must be used in order to achieve learning objectives. This study aims to describe the effect of the use of educational media Quizizz on student learning outcomes in the Aqidah Akhlak class VIII MTs Ar-Rofiqy Bogor Regency. This study uses a quantitative approach, using an experimental method, with a Quasi Experimental Design. The number of samples in this study were 64 students, which were divided into the experimental class usingeducational media Quizizz and the control class using conventional media. The instruments used are in the form of teacher and student activity sheets and test sheets. Data collection techniques carried out in the form of observation, documentation and tests. The results showed that the application ofeducational media Quizizz obtained 80% - 96% percentage data with very good interpretation. Based on the learning outcomes of the experimental class and control class students after treatment with an average score of 72.81 for the control class and 80.31 for the experimental class, the research data was analyzed using a t-test with an independent simple t-test. The data obtained shows > (2,457 > 2,000) so that there is a significant effect of learning outcomes between the control and experimental classes. So that the hypothesis testing can be concluded that there is a positive influence on the use ofeducational media Quizizz on student learning outcomes in the Aqidah Akhlak subject matter of social media etiquette in the view of Islam.